Collaborative Research: Resolving centennial- to millennial-scale trends in glacier extent and lake sedimentation in the Brooks Range, Arctic Alaska - Jason Briner; William D'Andrea; Darrell Kaufman (Arctic Data Center)
The goal of this collaborative project to reconstruct late Quaternary climate and glacier change in Arctic Alaska, one of few regions in the Arctic where mountain glaciers have left physical records of their former extent, making it valuable for comparing the timing and extent of mountain glacier variability between the lower latitudes and the Arctic. Several features of the climate and glacier history of the Brooks Range contrast with those from the North Atlantic region (which is often taken to represent the entire Northern Hemisphere in records of climate change) and currently available evidence indicates that the history of the Brooks Range more closely resembles glacier records from the southern Hemisphere. The investigators propose to develop records of climate change from lake sediments and records of glacier fluctuations using proglacial lake sediments and beryllium-10 dating of glacial features to address questions centered around four intervals of pronounced global change: (1) Last Glacial Maximum: Did glaciers retreat and temperatures increase in Arctic Alaska during the global LGM, as has been simulated by climate models? (2) Deglaciation: To what extent did climate change in Arctic Alaska coincide with North Atlantic climate fluctuations during deglaciation? (3) Holocene Glaciation: What was the extent of glaciers during (a) the Holocene thermal maximum, and (b) Neoglaciation? (4) Little Ice Age: Was it wetter or drier in the Brooks Range? The research will take place in suitable valleys (floatplane accessible valley with extant glaciers) in the north central Brooks Range. The project has several educational components, including support four graduate students and several undergraduate students and visits to the community of Anaktuvuk Pass to deliver presentations on climate research and the Brooks Range. The proposed research aims to produce well-dated and quantitative records of glacier and climate variability in the northernmost glaciated region of the U.S. Documenting the past behavior of arctic glaciers when subject to extreme climate events during the late glacial period and warm intervals like the Holocene can provide valuable insight to help better predict responses to future change.